2003
DOI: 10.1029/2002jd002808
|View full text |Cite
|
Sign up to set email alerts
|

Structural characteristics of rain fields

Abstract: [1] This paper analyzes the shape of rain area size distributions (RASDs) observed by radar in tropical and midlatitude regions. The rain area is defined, with respect to a rain threshold t, as the area, inside a contour, where the rain rate is higher than t. The size considered is the diameter of the equivalent circular area D. The reflectivity peaks inside the rain areas are numbered and the rain areas put together by classes having the same peak number. The size distributions of the rain areas containing th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
1

Year Published

2003
2003
2018
2018

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 57 publications
(103 reference statements)
0
19
1
Order By: Relevance
“…Previous studies revealed that lognormal distributions were frequently observed (López 1977;Houze and Cheng 1977;Mapes and Houze 1993;Mesnard and Sauvageot 2003;Cetrone and Houze 2006;Holder et al 2008). Other functional forms such as a power law (Machado and Rossow 1993), a double power law (Benner and Curry 1998), and an exponential form (Mesnard and Sauvageot, 2003) were also reported.…”
Section: Introductionmentioning
confidence: 98%
“…Previous studies revealed that lognormal distributions were frequently observed (López 1977;Houze and Cheng 1977;Mapes and Houze 1993;Mesnard and Sauvageot 2003;Cetrone and Houze 2006;Holder et al 2008). Other functional forms such as a power law (Machado and Rossow 1993), a double power law (Benner and Curry 1998), and an exponential form (Mesnard and Sauvageot, 2003) were also reported.…”
Section: Introductionmentioning
confidence: 98%
“…Mesnard and Sauvageot [2003] answered this question and showed that the RCSD is in fact best fitted by a lognormal function, whose modal value is less than about 2 km, that is located at a diameter smaller than the minimum size that can be resolved by most of the radars at the farthest part of their observation area. In such a way, (2) corresponds to the analytical fitting of a (lognormal) distribution truncated on the left, at size larger than the modal value, so that the validity domain of (2) has to be restrained to the diameter interval 2 km D 20 km.…”
Section: Distribution Of the Rain Cell Diametermentioning
confidence: 99%
“…[15] Many authors [Dennis and Fernald, 1963;Miller et al, 1975;Konrad, 1978;Goldhirsh and Musiani, 1986;Tenorio et al, 1995;Sauvageot et al, 1999;Mesnard and Sauvageot, 2003] have considered that rain cells can be approximated by a circular shape. The diameter of the circular cell of equivalent area is used as a characteristic measure of the rain cell size.…”
Section: Distribution Of the Rain Cell Diametermentioning
confidence: 99%
“…Figure 2 can be seen as a typical example. Nevertheless, from radar observations of rain fields in tropical and midlatitudes areas, Mesnard and Sauvageot [2003] show that 95% of the rain cells having an equivalent diameter smaller than 5 km -which represents the majority of the cells -are single-peaked. Moreover, they show that, in average, the relative frequency of the rain cell as a function of their peak number p, that is N A (p), is well-approximated by the power distribution:…”
Section: Rain Cell Definitionmentioning
confidence: 99%
“…Thus, for example, many authors have developed empirical or statistical models of rain cell size distribution based on radar measurements [Konrad, 1978;Goldhirsh and Musiani, 1986;Crane, 1996;Mesnard and Sauvageot, 2003].…”
Section: Introductionmentioning
confidence: 99%